2012
DOI: 10.1111/j.1464-410x.2012.11268.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer diagnosis is associated with an increased risk of erectile dysfunction after prostate biopsy

Abstract: What's known on the subject? and What does the study add? There have been several studies that have suggested there may be a relationship between prostate biopsy and erectile function and LUTS. Previous studies have suggested a specific association between the type of local anaesthesia administered and/or the number of biopsies performed. Other studies have suggested an exacerbation of LUTS after prostate biopsy. The present study identifies a positive cancer diagnosis as a novel characteristic that may expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 21 publications
4
26
1
5
Order By: Relevance
“…These data also suggests that older men (≥60 years) are predisposed to a worse erectile outcome after biopsy, therefore in this population, prostate biopsy should be used even more cautiously and physician-to-patient counselling should include this potential outcome in more detail. Similar to a study in March 2012, we found that those who had a final prostate cancer diagnosis were more likely to have a decline in IIEF-5 score after biopsy [16]. The exact mechanism of this decline in IIEF-5 score for these patients is most likely multifactorial in nature and many factors including psychogenic causes, fear of results, anxiety related to biopsy and even anatomical considerations including nerve damage and haematoma have potential in being related.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These data also suggests that older men (≥60 years) are predisposed to a worse erectile outcome after biopsy, therefore in this population, prostate biopsy should be used even more cautiously and physician-to-patient counselling should include this potential outcome in more detail. Similar to a study in March 2012, we found that those who had a final prostate cancer diagnosis were more likely to have a decline in IIEF-5 score after biopsy [16]. The exact mechanism of this decline in IIEF-5 score for these patients is most likely multifactorial in nature and many factors including psychogenic causes, fear of results, anxiety related to biopsy and even anatomical considerations including nerve damage and haematoma have potential in being related.…”
Section: Discussionsupporting
confidence: 83%
“…When evaluating LUTS with the IPSS (mild, total score 0-7; moderate, [8][9][10][11][12][13][14][15][16][17][18][19]; and severe, 20-35) at baseline compared with the other time-points, similar results were found. The mean IPSS at baseline was 10.2.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Ageing is commonly associated with the development of prostate cancer and progressive erectile dysfunction (ED). Patients with prostate cancer commonly experience an increased rate of ED at baseline (Feldman et al, 1994;Hoffman, 2011;Johansson et al, 2011;Helfand et al, 2012). Similarly, sexual dysfunction (SD) is prevalent among ageing males and is associated with reduced quality of life and sense of well-being (Laumann et al, 1999;Kushiro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Daha önceki çalışmalarda >60 yaş , daha önce biopsi öyküsü, prostat kanseri teşhisi olması, aktif izlemde olmasıvve biopside alınan kor sayısı ED riskini artıran durumlar olarak ortaya koyulmuştur (8,11,12,13). Bizim sonuçlarımızda <60 ve >60 yaş olanlarda ED riski bakımından anlamlı farklılık saptanmamıştır.…”
Section: Discussionunclassified